Asymmetric synthesis of aryloxypropanolamines via OsO4-catalyzed asymmetric dihydroxylation - Sayyed, I. A.; Thakur, V. V.; Nikalje, M. D.; Dewkar, Gajanan; Kotkar, S. P.; Sudalai, A. (Tetrahedron, 2005)
A simple and effective procedure for the enantioselective synthesis of several beta-adrenergic blocking agents incorporating the first asymmetric synthesis of celiprolol, is described. The key steps are (i) sharpless asymmetric dihydroxylation of aryl allyl ethers to introduce chirality into the molecules and (ii) conversion of cyclic sulfates into the corresponding epoxides using a three-step procedure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: antihypertensive; asymmetric dihydroxylation; cyclic sulfates; epoxides

Enantioselective synthesis of (S)-alpha-arylpropionic acids via pd-catalyzed kinetic resolution of benzylic alcohols - Thakur, V. V.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
A convenient synthetic route for the synthesis of three (S)-alpha-propionic acids, (S)-naproxen (90% ee), (S)-ibuprofen (82% ee) and (S)-phenylpropioilic acid (92% ee) is described. Pd-catalyzed oxidative kinetic resolution of the corresponding benzylic alcohols is used as a key step to introduce stereogenicity into the molecule.

Facile direct conversion of aldehydes to esters and amides using acetone cyanohydrin - Raj, I. V. P.; Sudalai, A. (Tetrahedron Letters, 2005)
Aromatic aldehydes with electron-withdrawing groups undergo rapid reactions with a variety of alcohols and secondary amines to afford the corresponding esters and amides, respectively, in high yields, when treated with NaCN or acetone cyanohydrin and base under ambient reaction conditions. In case of alpha,beta-unsaturated aldehydes, simultaneous reduction of the C=C bond along with esterification occurred to produce the saturated esters in high yields. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: amidation; esteritication; reduction; sodium cyanide

NaIO4-mediated C-H activation of alkylbenzenes and alkanes with LiBr - Shaikh, T. M.; Sudalai, A. (Tetrahedron Letters, 2005)
NaIO4 oxidizes lithium bromide efficiently under acidic conditions to functionalize alkylbenzenes and alkanes and produce the corresponding bromo and acetoxy derivatives in excellent yields. The protocol also demonstrates the direct conversion of cyclohexane into trans-1,2-dibromocyclohexane in moderate yield. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: alkanes; alkylbenzenes; C-H activation; Lithium bromide; NaIO4

NalO(4)/LiBr-mediated diastereoselective dihydroxylation of olefins: a catalytic approach to the prevost-woodward reaction - Emmanuvel, Lourdusamy; Shaikh, T. M. A.; Sudalai, A. (Organic Letters, 2005)
LlBr catalyzes efficiently the dihydroxylation of alkenes to afford syn and anti diols with excellent diastereoselectivity depending upon the use of NaIO4 (30 mol %) or Phl(OAc)(2) (1 equiv), respectively, as the oxidants. The oxidation of non-benzylic halides has been achieved for the first time to afford the corresponding diols in excellent yields.

NBS-catalyzed hydroamination and hydroalkoxylation of activated styrenes - Talluri, S. K.; Sudalai, A. (Organic Letters, 2005)
N-Bromosuccinimide efficiently catalyzes the hydroamination and hydroalkoxylation of activated styrenes using tosylamides, carbamates, and alcohols as the nucleophiles to afford amino and ether derivatives, respectively. Both the processes give good to excellent yields of the products with 100% regioselectivity (Markovnikov fashion).

Pd-catalyzed oxidative kinetic resolution of 2-azido-1-arylethanols - Sayyed, I. A.; Kumar, N. S. C. R.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
(-)-Sparteine/Pd (II) complex in combination with oxygen as a stoichiometric oxidant, catalyses the oxidative kinetic resolution of P-azido alcohols to afford the corresponding chiral 2-azido-1-arylethanols.
Keywords: (-)-sparteine-Pd (II) complex; beta-azidoalcohol; chiral 2-azido-1-arylethanol; Kinetic resolution

Titanium superoxide catalyzed selective oxidation of phenols to p-quinones with aq. H2O2 - Dewkar, Gajanan; Shaikh, T. M.; Pardhy, S.; Kulkarni, S. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
Titanium superoxide, a novel heterogeneous and readily accessible catalyst, is found to catalyze the selective oxidation of phenols to the corresponding 1,4-benzoquinones in preparative yields with aq. 30% H2O2 as oxidant under mild reaction conditions.

Co-catalyzed reductive cyclization of azido and cyano substituted alpha,beta-unsaturated esters with NaBH4: enantioselective synthesis of (R)-baclofen and (R)-rolipram - Paraskar, A. S.; Sudalai, A. (Tetrahedron, 2006)
Sodium borohydride in combination with a catalytic amount of CoCl, has been found to be an excellent catalytic system in reductive cyclizations of suitably substituted azido and cyano groups of alpha,beta-unsaturated esters to afford gamma and delta-lactams in high yields. The process has been demonstrated for the enantioselective synthesis of (R)-baclofen, (R)-rolipram, and (R)-4-fluorophenylpiperidinone, a key intermediate for (-)-paroxetine. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Asymmetric synthesis; cobalt chloride; gamma and delta-lactams; reduction; sodium borohydride

Green protocol for the synthesis of N-oxides from secondary amines using vanadium silicate molecular sieve catalyst - Phukan, P.; Khisti, R. S.; Sudalai, A. (Journal of Molecular Catalysis A-Chemical, 2006)
Vanadium silicate molecular sieve catalyst VS-I was found to promote efficiently the oxidation of alpha alpha,alpha'alpha'-tetrasubstituted secondary amines with 30% aqueous hydrogen peroxide as oxidant. In comparison to other catalysts reported to date, this heterogeneous catalyst offers a remarkably simple workup procedure and is reusable without any appreciable loss of activity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heterogeneous catalyst; Hydrogen peroxide; N-oxide; VS-1; zeolite

Natural kaolinitic clay: a remarkable catalyst for highly regioselective chlorination of arenes with Cl-2 or SO2Cl2 - Jayachandran, B.; Phukan, P.; Daniel, Thomas; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Natural kaolinitic clay containing transition metals such as Fe and Ti in its lattice has been found to exhibit unusual regioselectivity in the liquid-phase chlorination of arenes with either Cl-2 or SO2Cl2 as the chlorinating agent para-Chlorinated products are predominant for most of the substrates with an exceptional case of ortho-selectivity for the chlorination of aniline.
Keywords: Aniline; chlorination; chlorine; ortho-chloroaniline; sulfuryl chloride

Asymmetric synthesis of (R)-(-)-baclofen via asymmetric dihydroxylation - Thakur, V. V.; Paraskar, A. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
A short and efficient asymmetric synthesis of (R)-(-)-baclofen, a selective GABA(B) agonist has been described with an overall yield of 14% and 85% ee. The Os-catalyzed Sharpless asymmetric dihydroxylation of alpha,beta-unsaturated olefin constitutes the key step in introducing stereogenic centers into the molecule.
Keywords: asymmetric dihydroxylation; baclofen; cyclic sulfate; gamma-aminobutyric acid; Parkinsons' disease

Organocatalytic activation of TMSCN by basic ammonium salts for efficient cyanation of aldehydes and imines - Raj, I. Victor Paul; Suryavanshi, Gurunath; Sudalai, A. (Tetrahedron Letters, 2007)
Basic ammonium salts act as highly effective catalysts for the cyanosilylation of aldehydes and in Strecker-type aminonitrile synthesis using TMSCN as cyanide source at 25 degrees C under extremely mild conditions, affording very good to excellent yields of silylated cyanohydrins and alpha-aminonitriles. (C) 2007 Published by Elsevier Ltd.
Keywords: aldehydes; aminonitriles; cyanohydrin; cyanosilylation; multicomponent reactions; TMSCN

Sulfonamide- and hydrazine-based palladium catalysts: stable and efficient catalysts for C-C coupling reactions in aqueous medium - Kumar, N. S. C. Ramesh; Raj, I. Victor Paul; Sudalai, A. (Journal of Molecular Catalysis A-Chemical, 2007)
Syntheses of a novel family of sulfonamide-based palladium complexes and phenylhydrazine-based palladacycles are described. These catalysts are thermally stable, and not sensitive to air and moisture and some are completely soluble in water. These catalysts have shown excellent activity (good yields and high turnover numbers) and product selectivity in several arylation reactions including Suzuki, Heck, and Sonogashira reactions carried out totally under aqueous conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: arylation reaction; Heck reaction; palladium catalyst; Sonogashira reaction; Suzuki coupling reaction

Asymmetric synthesis of (S)-vigabatrin (R) and (S)-dihydrokavain via cobalt catalyzed hydrolytic kinetic resolution of epoxides - Raj, I. Victor Paul; Sudalai, A. (Tetrahedron Letters, 2008)
A concise route to the asymmetric synthesis of (S)-vigabatrin(R) and (S)-dihydrokavain has been described using Co-catalyzed hydrolytic kinetic resolution of racemic epoxides and regiospecific opening of terminal epoxides with dimethylsulfonium methylide as the key steps. (C) 2008 Elsevier Ltd. All rights reserved.

Efficient, rapid synthesis of bis(indolyl)methane using ethyl ammonium nitrate as an ionic liquid - Mulla, Shafeek Abdul Rashid; Sudalai, A.; Pathan, Mohsinkhan Y.; Siddique, Shafi A.; Inamdar, Suleman M.; Chavan, Santosh S.; Reddy, R. Santosh (RSC Advances, 2012)
A simple and rapid protocol has been developed for an efficient synthesis of bis( indolyl)methane in excellent yields using ethyl ammonium nitrate (EAN) as reusable ionic liquid at room temperature. The protocol involves an electrophilic substitution reaction of indoles with several aldehydes.

Oxidant controlled regio- and stereodivergent azidohydroxylation of alkenes via I-2 catalysis - Prasad, P. K.; Reddi, R. N.; Sudalai, A. (Chemical Communications, 2015)
A novel, I-2 catalyzed regio-and stereodivergent vicinal azidohydroxylation of alkenes leading to 1,2-azidoalcohols in high yields (up to 92%) and excellent dr (up to 98%) has been developed. This unprecedented transformation employs NaN3 and DMF as N-and O-nucleophiles respectively. The role of DMF as the O-source in the reaction has been unequivocally proven by O-18 labelling studies.

Titanium superoxide - a stable recyclable heterogeneous catalyst for oxidative esterification of aldehydes with alkylarenes or alcohols using TBHP as an oxidant - Dey, Soumen; Gadakh, Sunita K.; Sudalai, A. (Organic & Biomolecular Chemistry, 2015)
Titanium superoxide efficiently catalysed the oxidative esterification of aldehydes with alkylarenes or alcohols, under truly heterogeneous conditions, to afford the corresponding benzyl and alkyl esters in excellent yields. Mechanistic studies have established that this ``one pot'' direct oxidative esterification process proceeds through a radical pathway, proven by a FTIR spectral study of a titanium superoxide-aldehyde complex as well as spin trapping experiments with TEMPO. The intramolecular version of this protocol has been successfully demonstrated in the concise synthesis of 3-butylphthalide, an anti-convulsant drug.

Rhodium-catalyzed ortho C-H bond activation of arylamines for the synthesis of quinoline carboxylates - Gadakh, Sunita K.; Dey, Soumen; Sudalai, A. (Organic & Biomolecular Chemistry, 2016)
The rhodium catalyzed annulation of anilines with alkynic esters allowing for the high-yield synthesis of quinoline carboxylates with excellent regioselectivity is described. This unprecedented reaction employs either formic acid as the C1 source and reductant or copper(II) as the oxidant and is proposed to proceed via rhodacycle of in situ generated amide and enamine ester followed by ortho C-H activation of arylamines with rhodium as the catalyst.

Ti-superoxide catalyzed oxidative amidation of aldehydes with saccharin as nitrogen source: synthesis of primary amides - Kamble, Rohit B.; Mane, Kishor D.; Rupanawar, Bapurao D.; Korekar, Pranjal; Sudalai, A.; Suryavanshi, Gurunath (RSC Advances, 2020)
A new heterogeneous catalytic system (Ti-superoxide/saccharin/TBHP) has been developed that efficiently catalyzes oxidative amidation of aldehydes to produce various primary amides. The protocol employs saccharin as amine source and was found to tolerate a wide range of substrates with different functional groups. Moderate to excellent yields, catalyst reusability and operational simplicity are the main highlights. A possible mechanism and the role of the catalyst in oxidative amidation have also been discussed.